ANALISA HUBUNGAN LEADERSHIP STYLE TERHADAP LEARNING ORGANIZATION DALAM MENINGKATKAN FINANCIAL PERFORMANCE PADA SEKTOR PERHOTELAN DI JAWA TIMUR - Suryono, Frandita Ameliasari (Business Accounting Review, 2016)
This study aimed to examine the direct and significant influence of leadership style to learning organization, learning organization to financial performance, and leadership style to financial performance on hospitality sector in East Java. This study used quantitative approach and the data were obtained through the distribution of questionnaire to three-star hotel until five-star hotel in East Java. The data that were obtained, then processed by using PLS software. The result of this study showed that there was a positive and significant relationship of leadership style to learning organization, learning organization to financial performance, leadership style to financial performance on hospitality sector in East Java. Learning organization could become as intervening variables to leadership style and financial performance because of the direct relationship between leadership style and financial performance gave smaller influence than through learning organization.